Trypanosoma cruzi-specific IFN-γ-producing cells in chronic Chagas disease associate with a functional IL-7/IL-7R axis - Natale, Maria Ailen (2018)
Background: The severity of cardiac disease in chronic Chagas disease patients is associated with different features of T-cell exhaustion. Here, we assessed whether the ability of T cells to secrete IFN-γ in response to T. cruzi was linked to disruption in immune homeostasis and inflammation in patients with chronic Chagas disease. Methodology/Principal findings: PBMCs from chronic Chagas disease patients and uninfected controls were examined for frequencies of T. cruzi-responsive IFN-γ-producing cells by ELISPOT and cellular expression and function of IL-7R using flow cytometry. Serum levels of IL-7, IL-21, IL-27, soluble IL-7R, and inflammatory cytokines were also evaluated by ELISA or CBA techniques. Patients possessing T. cruzi-specific IFN-γ-producing cells (i.e. IFN-γ producers) had higher levels of memory T cells capable of modulating the alpha chain of IL-7R and an efficient response to IL-7 compared to that in patients lacking (i.e. IFN-γ nonproducers) parasite-specific T-cell responses. IFN-γ producers also showed low levels of soluble IL-7R, high basal expression of Bcl-2 in T cells and low basal frequencies of activated CD25+ T cells. Modulation of IL-7R was inversely associated with serum IL-6 levels and positively associated with serum IL-8 levels. Circulating IL-21 and IL-27 levels were not associated with the frequency of IFN-γ producing cells but were reduced in less severe clinical forms of the disease. In vitro stimulation of PBMCs with IL-7 or IL-27 enhanced IFN-γ production in IFN-γ producers but not in IFN-γ nonproducers. Conclusions/Significance: Alterations of the IL-7/IL-7R axis and in the levels of inflammatory cytokines were linked to impaired T. cruzi-specific IFN-γ production. These alterations might be responsible of the process of immune exhaustion observed in chronic Chagas disease.